Strategies in sample preparation for proteome analysis of biological fluids from water buffaloes - BALHARA, ASHOK KUMAR; SANGWAN, SUMAN; GHOSH, MAYUKH; KUMAR, RAJESH; PHULIA, S K; SINGH, INDERJEET (The Indian Journal of Animal Sciences, 2023)
Livestock species such as water buffalo have some unique characteristics like high fat percentage in milk and plasma, poor sample generation, peculiar behaviour, etc. making it difficult for proteomic analysis of such samples. Additionally, there is a limited database in terms of identified proteins, characterised antibodies and functional attributes of known molecules specific to buffalo. The body fluids like blood, milk, urine and foetal fluids offer a great opportunity in understanding physio-pathological processes and thus aid in developing reliable diagnostics. Standardised sample preparation protocols are key to advancement of proteomics science. Optimising sample preparation for 2-DE proteomics in buffalo serum, milk, and foetal fluids is crucial. Commercially available kits or laboratory methods for clean-up, enrichment, and condition optimising can be applied for getting optimum results. The 2-D clean up strategy is an important step in sample preparation procedures to get rid of inferring substances which hamper IEF. The sample preparation of the buffalo biological fluids (serum, foetal fluids, maternal uterine flushing and milk samples) reported in the present study shall provide valuable information for further research.